Effects of sintering atmospheres on sintering behavior, electrical conductivity and oxygen permeability of mixed-conducting membranes - Chang, X.; Zhang, C.; Dong, X.; Zhou, W.; Jin, W.; Shao, Zongping; Xu, N. (Elsevier BV, 2008)
Effects of sintering atmospheres on properties of SrCo0.4Fe0.5Zr0.1O3-d mixed-conducting membranes were in detail studied in terms of sintering behavior, electrical conductivity and oxygen permeability. The sintering atmospheres were 100% N2, 79% N2-21% O2, 60% N2-40% O2, 40% N2-60% O2, 20% N2-80% O2 and 100% O2 (in vol.%), and the prepared membranes were correspondingly denoted as S-0, S-21, S-40, S-60, S-80 and S-100, respectively. It was found that the properties of membranes were strongly dependent on the sintering atmosphere. As the oxygen partial pressure in the sintering atmosphere (PO2) increased, sintering ability, electrical conductivity and oxygen permeability decreased at first, which was in the order of S-0 > S-21 > S-40. However, as PO2 increased further, sintering ability, electrical conductivity and oxygen permeability increased gradually: S-40 < S-60 < S-80 < S-100. And the S-100 membrane had the best sintering ability, electrical conductivity and oxygen permeability in all membranes. © 2007 Elsevier B.V. All rights reserved.